Impact of GST on Impulsive Buying Behavior of Consumer on FMCG (Fast Moving Consumer Goods) - Mr. Manoj Gaurav,Dr. Vikram Sandhu,Dr. Sukhpreet kaur (International Journal of Advanced Science and Technology, 2020)
There are many indirect tax reforms in Indirect tax structure and Goods and Service Tax(GST) is one of the major reforms since 1947. GST is a Destination Based Tax, which states that it is charged at the place where goods are supplied. It is based on Dual Tax system, which means both central and state government will share the amount of tax. The share which is retained by central government is known as Central Goods and Service Tax (CGST) and the share which is retained by state is known as State Goods and Service Tax (SGST). The purpose of GST is to replace many other indirect taxes to bring uniformity in India with the objective of bringing one tax for one nation. The paper highlights the background and the impact of GST on FMCG, which is the 4th largest sector in Indian economy and consist of 50 per cent Food and Beverage sector and 30 per cent is Household and Personal care. The paper further explores various benefits and opportunities of GST. Finally, the paper examines and draws out a conclusion.